Fully remote intensive trauma-focused treatment for PTSD and Complex PTSD. Issue 2 (19th December 2022) - Bongaerts, H.; Voorendonk, E. M.; Van Minnen, A.; Rozendaal, L.; Telkamp, B.S.D.; de Jongh, A.
ABSTRACT: Background: It is unknown whether remotely delivered intensive trauma-focused therapy not only is an effective treatment for PTSD, but also for Complex PTSD. Objective: Testing the hypothesis that a brief, fully remotely administered intensive trauma-focused treatment programme for individuals with PTSD and Complex PTSD would be safe, and associated with a significant decline of the corresponding symptoms and diagnostic status. Method: The treatment sample consisted of 73 consecutive patients diagnosed with PTSD according to the CAPS-5. According to the ITQ ( n  = 70) 33 (47.1%) patients also fulfilled the diagnostic criteria of Complex PTSD. The 4-day treatment programme contained a combination of prolonged exposure, EMDR therapy, physical activities and psycho-education. Treatment response was measured using the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5), the PTSD Checklist for DSM-5 (PCL-5), and the International Trauma Questionnaire (ITQ) for classifying Complex PTSD and indexing disturbances in self-organization (DSO). Results: Overall CAPS-5, PCL-5, and ITQ-DSO scores decreased significantly from pre- to post-treatment (Cohen's ds 2.12, 1.59, and 1.18, respectively), while the decrease was maintained to six months follow-up. At post-treatment, 60 patients (82.2%) no longer met the diagnostic criteria of PTSD, while the proportion of patients with Complex PTSD decreased from 47.1% to 10.1%. No drop out, and no personal adverse events occurred. Conclusions: The results support the notion that intensive, trauma-focused treatment is feasible, safe and associated with a large decrease in PTSD and Complex PTSD symptoms, even when it is brief, and applied fully remote. HIGHLIGHTS Second study to examine the effectiveness of a fully remote intensive trauma-focused treatment for PTSD and Complex PTSD. Significant decrease of DSO symptoms. Over 80 percent of the patients no longer met the diagnostic criteria of PTSD and Complex PTSD following treatment.